2015
DOI: 10.1186/s13601-015-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

Accidental exposures to peanut in a large cohort of Canadian children with peanut allergy

Abstract: BackgroundWe previously estimated that the annual rate of accidental exposure to peanut in 1411 children with peanut allergy, followed for 2227 patient-years, was 11.9% (95% CI, 10.6, 13.5). This cohort has increased to 1941 children, contributing 4589 patient-years, and we determined the annual incidence of accidental exposure, described the severity, management, location, and identified associated factors.FindingsChildren with physician-confirmed peanut allergy were recruited from Canadian allergy clinics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 29 publications
2
55
0
Order By: Relevance
“…From another study on pediatric peanut allergy in Canada, anaphylaxis was found in 36.7%20). Within patients who were sensitized to BW, 29.2% had anaphylaxis in Italy21).…”
Section: Discussionmentioning
confidence: 97%
“…From another study on pediatric peanut allergy in Canada, anaphylaxis was found in 36.7%20). Within patients who were sensitized to BW, 29.2% had anaphylaxis in Italy21).…”
Section: Discussionmentioning
confidence: 97%
“…However, avoidance of peanuts, nuts, and seeds can be very difficult for the sensitized individuals due to several factors such as ubiquitous use of peanut and peanut ingredients in food processing industries, unintentional contamination, unawareness, and cross contaminations (Joyce et al, 2006). Most cases of adverse events are apparently due to the accidental ingestion that is increasing despite increased awareness (Al-Muhsen, Clarke, & Kagan, 2003;Cherkaoui et al, 2015;Joyce et al, 2006). In addition, undeclared allergens are a big cause of food recalls from the market according to the report by the US Food and Drug Administration (FDA) and others (Ashley et al, 2018;Vandekerckhove et al, 2017), which is another serious issue for food manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in Japan, peanuts account for 4.6% of food anaphylactic antigens [5]. Even a trace amount of peanut ingestion can cause anaphylaxis [6]; the annual rate of accidental ingestion is reported to be 12% among Canadian patients with peanut allergy [7]. Basic management for food allergic patients with a history of anaphylaxis is to avoid causative foods while waiting for natural tolerance acquisition [8].…”
Section: Introductionmentioning
confidence: 99%